A transição para a assimetria regulatória e os mecanismos de sustentabilidade deste modelo: uma análise dos aeroportos concedidos e dos aeroportos autorizados - Torres, Maíra Ayres (2015)
The present study is developed to analyze the asymmetric regulation model from two specific problems: the mechanisms required to obtain an asymmetric environment, as well as the manner in which to orchestrate such a model, in order to reconcile sustainable coexistence in a hybrid structure of competition. Changing a symmetric regulation environment observed shall be the way can be promoted to an asymmetric environment, safeguarding the rights and obligations of providers of certain activity. Moreover, it will seek to suggest legal instruments to allow the composition of two ways to undertake an economic activity, one who will take under public law (publicatio); and another that relates to private law (ordenatio); comprising well, assymetric regulation. As an illustration, will be verified the provisional measure (MP) 656/14 - which provided a possible model in which they would have two airport infrastructure offerings - to better exemplify how, legally, can make this organization possible dual delivery, via government (or delegatee), in the form of 'concessão'; and the private sector, according to 'autorização'.